Groundwater recharge from heavy rainfall in the southwestern Lake Chad Basin: evidence from isotopic observations. Issue 8 (11th June 2021) - Goni, Ibrahim Baba; Taylor, Richard G.; Favreau, Guillaume; Shamsudduha, Mohammad; Nazoumou, Yahaya; Ngounou Ngatcha, Benjamin
ABSTRACT: We examine groundwater recharge processes and their relationship to rainfall intensity in the semi-arid, southwestern Lake Chad Basin of Nigeria using a newly compiled database of stable isotope data (δ 2 H, δ 18 O) from groundwater and rainfall. δ 18 O signatures in groundwater proximate to surface waters are enriched in 18 O relative to regional rainfall and trace focused groundwater recharge from evaporated waters via ephemeral river discharge and Lake Chad; groundwater remote from river channels is comparatively depleted and associated with diffuse recharge, often via sand dunes. Stable isotope ratios of O and H (δ 2 H, δ 18 O) in groundwater samples regress to a value along the local meteoric waterline that is depleted relative to weighted mean composition of rainfall, consistent with rainfall exceeding the 60 th percentile of monthly precipitation intensity. The observed bias in groundwater recharge to heavy monthly rainfall suggests that the intensification of tropical rainfall under global warming favours groundwater recharge in this basin.